Antiviral properties of collagen-based corneal substitute incorporating sustained delivery system for anti-infective peptide LL37 (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To investigate in vitro the anti–Herpes Simplex Virus (HSV)-1 properties of the collagen-based corneal substitute (CCS) incorporating the sustained delivery system for anti-infective peptide (AIP) LL37.Methods: AIP LL37 was encapsulated into silica nanoparticles (SiNPs) under magnetic stirring. SiNPs with LL37 were then introduced into the CCS at the time of its fabrication by creating interpenetrating networks of type I collagen and phosphorylcholine. The anti-HSV-1 properties of the composite CCS were assessed by counting plaque forming units (PFU).Results: When the CCS incorporating the SDS for LL37 was added to the culture of human corneal epithelial cells (HCECs), virus concentration in the 24-h and 72-h culture media was less than 50 PFU/mL and 39333.3±9291.6 PFU/mL, respectively.  Concentration of HVS-1 in the 24-h and 72-h culture media for HCECs without CCS-based treatment was 2800±1928.7 PFU/mL and 221666.7±36855.6 PFU/mL, respectively (P24h = 0.039, Р72h = 0.063).Conclusion: The CCS incorporating the SDS for LL37 was efficacious within 24 h of culture, when used to block the spread of HSV-1 infection in vitro in HCECs. Additionally, the CCS remained efficacious at 24 h and 72 h of culture, when used for the prophilaxis of HSV-1 infection.
Keywords: artificial cornea; sustained delivery system; LL37; herpes simplex virus